OPTIMIZATION AND PHYSICAL STABILITY OF KEMBANG BULAN (Tithonia diversifolia [A.Gray] EXTRACT CREAM FORMULA - Diah Nur Kurnianingrum; Abdul Karim Zulkarnain (Universitas Muhammadiyah Magelang, 2023)
Based on recent studies, the ethanolic extract of Kembang Bulan leaves (Tithonia diversifolia[A.Gray]) has an anti-keloid effect. This study aims to determine the optimum formula for cream preparations with paraffinum liquidum, cetyl alcohol, and stearyl alcohol. Inappropriate comparison of additional ingredients results in the physical properties of the preparation becoming unstable during storage. The optimum formula was obtained from the optimization using Simplex Lattice Design (SLD) by software Design Expert version 10.0. The parameters measured were viscosity, pH, spreadability, adhesive ability, and accelerated study (centrifugation). The optimum cream formula consists of 19.11% b / b; Cetyl alcohol with a level of 2.01% b / b; stearyl alcohol with a level of 1.49% b / b with a viscosity of 134.35 dPa.s, a spread of 5.78 cm, pH 6.243, and adhesive ability of 13.61 seconds. The cream base produced is milky white, has a viscosity of 143.99 dPa.s, a spread of 5.7 cm, pH 6.305, and adhesion to 14.57 seconds. There is a significant difference in viscosity and pH of the experimental and software prediction. However, there is no significant difference in adhesive ability and spreadability response. The cream base and ethanolic extract of Kembang Bulan leaves have a significant difference in physical stability except for its spreadability. During the 4 weeks of storage, both of the creams are relatively stable. The cream is stable after centrifugation.